Edge Effect on Bird Community in Ternate, North Maluku, Indonesia - Tamnge, Fadila; Nurdin, Aqshan Shadikin; Baguna, Firlawanti Lestari; Kurniawan, Andy; Tamrin, Mahdi; Husen, Nurmila (Jurnal Manajemen Hutan Tropika, 2024)
The edge is a meeting place between two ecosystems, or it can also be interpreted as a boundary where two habitats meet and interact. The presence of edges can create an edge effect and increase richness and species abundance. In the present study, we analyzed how edge and vegetation diversity affect a) bird communities and b) how birds respond to edges. Observation plots were placed in jamblang stands and coconut plantations (edge and interior). Bird communities were observed using point counts with a fixed radius of 25 m, and the distance between plots was 50 m. A survey of vegetation diversity was conducted using a combination of the transect and plot methods. The research showed that the highest species richness and diversity of birds (128 individuals of 18 species) and vegetation (168 individuals of 20 species) were found at the edge, although there were only slight differences in the number of species in each habitat. This was influenced by the structure and composition of the vegetation at the observation site. Nevertheless, this proves that the edge effect shapes the composition of bird communities. There are 9 species of bird can be mapped into 4 response models: generalis neutral, generalist edge exploiter, specialist edge exploiter, and edge specialist.